Peningkatan Kepercayaan Diri dan Minat Kerja Staf Honor BPKAD Kab. Langkat Melalui Apresiasi dan Motivasi - Ramadhan, Taufiq; Widian Saragih, Mujahid (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
This study aims to investigate the impact of motivation and appreciation on enhancing individuals' self-confidence and work interest in the work environment. Self-confidence is defined as an individual's belief in his or her abilities and worth, while job interest includes interest in and commitment to one's work. This study aims to determine how motivation and appreciation strategies can contribute to increased self-confidence and more positive work interest. The location of the author's field work practice is on Jl. Khaiaril Anwar No.1, Kwala Bingai, Kec. Stabat, Langkat Regency, North Sumatra. And in this practice the stages used are the stages of intervention at the micro level, namely the stages of case work from Skidmore Thackeray and Farley in Adi (2005: 149) which consists of the research stage, the assessment stage, the intervention stage, and the termination stage. The results obtained from this practice activity show an increase in self-confidence and interest in the work of honorarium staff in the BPKAD Kab. Langkat.